RELATION BETWEEN THE INTENSITY OF THE SOUTH-WEST MONSOON AND THE OIL-SARDINE FISHERY OF INDIA - Murty, A V S; Edelman, M S (Indian Journal of Fisheries, 2011)
THE problem of fluctuations of marine fish populations and commercialstocks is a great concern of the marine fishery industries. The fluctuationsdepend upon the biological features of the individual species and theenvironmental factors. It is not possible to solve the problem withoutunderstanding both the aspects. The abundance of fish depends mainlyupon the feeding conditions especially in larval and juvenile stages. Andthe feeding conditions depend upon the primary production which conditionallydepends on the available nutrient salts in the sea. The availabilityof nutrients will much depend upon the vertical and horizontal circulationsin the sea.